Application of Crestal Anesthesia for Treatment of Class I Caries in Posterior Mandibular Teeth - Koroush Taheri Talesh; Shiva Solahaye Kahnamouii (Tabriz University of Medical Sciences, 2011)
Background and aims. Current infiltration techniques for achieving anesthesia in dental procedures are not applicable in posterior mandibular region because of its dense cortical bone. The aim of this study was to evaluate the efficacy of a specific infiltration anesthesia in posterior mandibular teeth instead of inferior alveolar nerve block for restorative procedures. Materials and methods. Crestal anesthesia (CA) was assessed both clinically and by computed tomography scan for its efficacy and side effects. A combination of an opaque material (Ultravist) and 2% lidocaine was used to trace the anesthetic solution. The combination was primarily injected in the gingival tissue of rabbit and was followed-up regularly for two weeks to assess any possible injury. After confirming its safety, a combination of these materials was injected to volunteers to assess efficacy and diffusion route. A total of 154 patients (77 female, 77 male) with matched bilateral posterior teeth in mandible were selected randomly and an IANB and CA were performed randomly and separately in different sessions for the contra lateral teeth. The onset of anesthesia, anesthesia duration, pain, blood pressure, pulse rate, and consumed volume of anesthetic solution was recorded for each technique. Data were analyzed using paired t-test. Results. There were no significant differences in clinical attachment loss, pocket depth, bone level, plaque index, and free gingival margin between the two flaps (p>0.05). Conclusion. CA could be considered as a reliable and safe primary injection in posterior mandibular teeth for restorative treatments.